In vitro antifungal activity of the leaf extract of Tectona grandis L. f. - Lazo-Pérez, Yamila (2026)
Introduction. The development of biofungicides from plant extracts represents an alternative for addressing fungal resistance. The aqueous extract of Tectona grandis L. f. leaves could constitute a source of bioactive metabolites with potential phytosanitary application. Objective. To evaluate the in vitro antifungal activity of the aqueous leaf extract of Tectona grandis L. f. against Fusarium sp. and Curvularia sp. using response surface methodology, in order to generate a predictive model to estimate the antifungal response under the study conditions. Materials and methods. The research was conducted in the province of Pastaza, Ecuador, from January to May 2023. The aqueous leaf extract was obtained from T. grandis leaves and evaluated using the poisoned medium technique. An experimental design based on I-optimal response surface methodology was applied and configured with the Coordinate Exchange algorithm. The factors studied were the extract concentration (40Ð75 mg/mL) and fungal strain type. The response variable was the percentage of mycelial growth inhibition. The model was validated through analysis of variance. Results. The extract showed concentration-dependent antifungal activity against both strains. Maximum inhibition was observed at 75 mg/mL, with 100 % for Fusarium sp. and 50 % for Curvularia sp. The cubic model described the nonlinear relationship between concentration and inhibition, with a coefficient of determination greater than 0.98 and significant quadratic and cubic terms (p < 0.05). Conclusions. The freeze-dried aqueous extract of T. grandis leaves showed potential as a biofungicide, with greater efficacy against Fusarium sp. The fitted model enables prediction of the antifungal response and its potential application in sustainable phytosanitary management strategies.